Enhancing Public Speaking, Data Analysis, and Digital Financial Management Skills in the Society 5.0 Era - Muhammad Fajar B; Fitriyanty Dwi Lestary; Sukma Riski Ananda; Muwaffiq Nurimansyah Mapparenta; Dewi Fatmawati Surianto (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community service program aims to strengthen the readiness of high school students in facing higher education challenges through capacity building on public speaking, data analysis, and digital financial management. The transition toward Society 5.0 demands students to possess strong communication skills, data literacy, and the ability to manage digital-based finance responsibly. The training was conducted through interactive lectures, hands-on practices, simulations, and mentoring sessions involving high school students. Results show an increase in students’ confidence in public speaking, improvement in basic data-analysis skills using digital tools, and better understanding of digital financial planning. This training has succeeded in providing practical knowledge and strengthening students’ readiness to continue to the university level. Future programs are expected to expand similar training to broader schools and integrate more advanced modules.